Surgical treatment of incarcerated paraesophageal hiatal hernia complicated by necrosis and perforation of the posterior gastric fundus - Kulyk, Viktoriia; Kritsak, Yuliana; Perepadya, Vladyslav; Nevmerzhytskyi, Viktor (The Ukrainian Scientific Medical Youth Journal, 2025)
the incidence of hiatal hernia is 15-20% in Western populations, with only 9% of patients having clinical manifestations of the disease [1, 2]. Risk factors for hiatal hernias include age (over 50 years), obesity, and male gender [3]. Complications of hiatal hernias, including incarceration, are rare pathological conditions. To present a clinical case of surgical treatment of incarcerated paraesophageal hiatal hernia complicated by necrosis and perforation of the posterior gastric fundus. Patient P., 71 years old, was taken by ambulance to the emergency department of general surgery with complaints of severe abdominal pain, nausea, repeated vomiting that did not bring relief, and general weakness. According to the clinical and laboratory (physical examination, complete blood count, complete urine analysis, biochemical blood test, indicators of the acid-base state of the blood) and instrumental (radiography of the abdominal and thoracic cavities) examinations, a preliminary diagnosis was established: Perforation of a hollow organ. Peritonitis. After preoperative preparation, the patient was taken to the operating room. A laparotomy was performed, during which a necrotic area measuring 5.0x4.0 cm with a perforation in the center measuring 1.0x1.0 cm, dilation of the esophageal opening of the diaphragm, and widespread serous-fibrinous peritonitis in the toxic stage were detected on the posterior wall of the fundus of the stomach. The scope of the operation: excision of the necrotic area with perforation and suturing of the posterior wall of the stomach fundus, sanitation and drainage of the abdominal cavity. Herniated hilum repair was not performed, given the presence of peritonitis and the patient's serious condition. The postoperative period was without complications. The patient was discharged from the hospital with improvement and recommendations for planned surgical treatment of diaphragmatic hernia. Thus, strangulation of paraesophageal hernias of the esophageal opening of the diaphragm is a rare pathological condition with a high risk of developing postoperative complications and fatal outcome. Timely diagnosis and treatment of hiatus hernias in a planned manner contribute to the prevention of complications and improve the prognosis for the quality of life of patients.